Population and Regions Extraordinary From Situations Protection in Doing Engineering Technical Events (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In this article population and regions extraordinary of situations negative from the effect protection in doing engineering technical measures solution doer role seeing developed _ It is natural disasters manage according to of literature present situation learns , protection to do for used different different engineering methods analysis does , practical studies the results present is enough and future to strategies effect discussion does _ Research innovative engineering solutions flexible teams to build and extraordinary situations consequences to soften how contribution to add about our understanding to increase directed.